Future‌ Studies‌ and‌ Application‌ of‌ International‌ Relation‌ Theories - Seyed Reza Mousavinia (رهیافتهای سیاسی و بین المللی)
How can we use international relations theory, which ends in prediction, in the future studies that ends up in the future making? What is the position of critical theories of international relations in the future studies? Future studies are defined in interpretative studies, due to its conception, the rotational attitude to history and the possibility of constructing future. According to some futurists, the use of the theoretical framework in interpretative studies is impossible. In contrast, some argue that the process of future studies is not just based on imagery and imagination, but there is an important pillar in future studies, which is past and present studies, then, to identify and explain trends and events, one can use the theory as explained and analyzed tools. In this research, wepresent the third perspective, by dividing the process of future studies into two exploratory and normative stages. we show that the use of the theoretical framework in the exploratory phase is possible but limited, but the exploitation of theories in the normative stage is crucial for future development. The hypothesis is: the extended present pattern in future studies is based on two stages: exploratory and normative: in the first stage, probable futures are discovered in a process with an inductive strategy. Restricting this stage in the theoretical framework creates an ontological limitation. But in the normative stage, a selection of theories can be used, especially the approach of theories to the future in the stages of scenario making and prescription.